Top athletes handedness in the major racket sports - Malagoli Lanzoni, I.; Semprini, G.; Di Michele, R.; Merni, F. (International Journal of Table Tennis Sciences, 2013)
Previous research showed a higher percentage of left-handed athletes in interactive and fast ball sports than in the general population. The aim of this study was to analyse the patterns of representation of left-handedness in top level competitors of the major racket sports. The hand used to hold the racket by the 100 world best male players (selected from 2012 rankings) in tennis (T), table tennis (TT), squash (S) and badminton (B) was recorded. The proportion of left-handers was calculated for each sport and logistic regression analyses were used to evaluate the probability for a player of holding the racket with the left hand given his position in the ranking. TT showed a higher percentage of left-handers (29%) than T (15%), B (16%) and S (14%). Logistic regressions showed that, when going up in the ranking, the probability of using the left-hand to hold the racket tended to increase in TT, B and S, and to decrease in T. The higher proportion of left-handers observed in TT when compared to the other sports can be attributed to the fact that, among the analysed sports, TT is a sport in which the opponents stand with the shortest distance. Furthermore, the technical and tactical components of performance are more determinant than physical fitness in TT, and these characteristics, taken together, may favor left-handed players. The very low number of left-handers among the very best tennis players may be explained by the fact that the disadvantage of a reduced experience against left-handed opponents is nowadays compensated by the player`s professionalism. In conclusion, the present study confirmed that left-handed individuals are more represented in racket sports, and especially in TT, when compared with the general population. Finally, considering the specific position of each player in the ranking as determinant of left-handedness probability seems to be a promising approach to further analyse left-handedness in the best ranked players of different sports.